HOW WE CAN TRUST MEASURES OF BPV SINCE IT'S VALUE IS SO VARIABLE ITSELF?. (June 2018) - Strocchi, E.; Mastini, M.; Rosticci, M.; Borghi, C.
Abstract : Objective: In recent years an increasing attention has been paid to blood pressure variability (BPV) because some evidence suggests that it is related to the presence of target organ damage and to the risk of cardiovascular events; home blood pressure (HOME BP) could be an easy way to evaluate medium-term variability as shown by the Ohasama study. However, very rarely HOME BP is measured regularly and/or recorded appropriately. One of our patient measured her BP almost every day for about 5 months (a total of 306 measures because some days she took more than one measurement); during this period the anti-hypertensive therapy was unchanged and the compliance was excellent (from the daily diary it was possible to confirm also a very regular life-style). Figure. No caption available. Design and method: We calculated average BP and BPV in subsets of these measures (morning vs evening and each month separately). Results: Overall BP control was excellent (average systolic BP = 120 mmHg; average diastolic BP = 81.8 mmHg) and BPV, measured as SD was 6.56 mmHg (CV = 5, 5%) for systolic and 4.99 mmHg (CV = 6.1%) for diastolic; while average BP was similar in the morning and in the evening, BPV was different (9.44 vs 8.46 mmHg) for systolic; moreover, BPV calculated on the HOME BP taken during each month was quite variable (from 5.15 to 8.5 mmHg, that is + 30% or −21% from the mean for systolic and from 3, 97 to 6.83 mmHg, that is +37% or – 20% from the mean for diastolic). We calculated also AVR (average real variability) in the different subsets with similar results. In Figure 1 we show the variable all-cause-mortality risk-increment during BP follow-up according to the recent published literature. Conclusions: We believe that the variability of BPV measures observed in this patient arises some doubts about its value as a prognostic index as it does not appear stable within the single patient. In other words BPV is too variable to be useful!